Electron beam induced etching of carbon nanotubes enhanced by secondary electrons in oxygen. (18th April 2017) - Yoshida, Hideto; Tomita, Yuto; Soma, Kentaro; Takeda, Seiji
Abstract: Multi-walled carbon nanotubes (CNTs) are subjected to electron-beam-induced etching (EBIE) in oxygen. The EBIE process is observed in situ by environmental transmission electron microscopy. The partial pressure of oxygen (10 and 100 Pa), energy of the primary electrons (80 and 200 keV), and environment of the CNTs (suspended or supported on a silicon nitride membrane) are investigated as factors affecting the etching rate. The EBIE rate of CNTs was markedly promoted by the effects of secondary electrons that were emitted from a silicon nitride membrane under irradiation by primary electrons. Membrane supported CNTs can be cut by EBIE with a spatial accuracy better than 3 nm, and a nanogap of 2 nm can be successfully achieved between the ends of two suspended CNTs.